UPDATE. JUNG & ERWACHSEN (TÂNĂR ŞI ADULT). NOUL PROGRAM OFERIT DE BIBLIOTECA MUNICIPALĂ DIN MÜNCHEN - MÜLLER, Biblioteca Municipală, München, Germania, Raphaela (BIBLIOPOLIS, 2020)
The author presents a new program for readers implemented in the Municipal Library of Munich, Germany. This program offers multidimensional concept for the development of media content and online special events with a focus on leisure. The beneficiaries are especially young people, and for them is made an offer of instructive educational activities longstanding at the ML in Munich. However, the program does not assume educational mission in the classical sense, but takes advantage of its contacts with educational and cultural institutions. The focus is put on the creative work combined with leisure and entertainment media, thus are realizing some multimedia teaching projects.